البلاغة الجديدة : حجاج بلاغي أم خطاب إقناعي؟ - علا, عبد الرزاق (University of El-oued, 2021)
ملخص: لقد أصبح مفهوم " البلاغة الجديدة " يتداخل كثيرا مع مفهوم"نظرية الحجاج" كونها شملت كل حقول المعرفة ؛ وحقلها –بلاغة الجديدة- لا يتوقف عند حدود دراسة الجانب العملي فقط، بل أصبح يرتبط بمفهوم الحجاج ،كما أنها أصبحت تنظر إلى الخطابات الإنسانية على أنها خطابات حجاجية تنجز أثناء العمليات التواصلية التي تهدف إلى التأثير في المتلقي ويمكننا أن نتقصى بلاغة الخطاب الحجاجي من الرسالة الموجه من المتكلم إلى لمتلقي لحظة الاستلام في شكل خطابات متنوعة ؛وعليه يتمظهر الخطاب الحجاجي من وجهة نظر البلاغة الجديدة عندما يحمل بذرة خلاف تتضمن قصدا تأثيريا مضمرا أو معلنا بنية تحويل أو تعديل وجهة تفكير المخاطب أو حمله على مزيد من مواقفه داخل مسار تواصلي غير إلزامي ؛ و أيّ خطابات نصنعها مهما كانت طبيعتها: سردية ،شعرية ، دينية أو قانونية ...أم غيرها من الخطابات حيثما وجدت فإنها تحمل في تضاعيف بنيتها الداخلية اللّسانية اللّغوية بُعدا حجاجيّا من منظور البلاغة الجديدة . -تروم هذه الورقة البحثية التنقيب عن المفاهيم الجديدة التي طرحتها البلاغة الجديدة عند النقاد والمفكرين المعاصرين. الكلمات المفتاحية: البلاغة الجديدة- بلاغة الخطاب – الخطاب الحجاجي - الخطاب ألإقناعي . Abstract: This paper examines the different points of view of critics and thinkers on the new concepts of theNew Rhetoric. The concept of New Rhetoric is overlapping significantly with the concept of the theory of argumentation, which encompasses different realms of knowledge. Furthermore, the New Rhetoric is not limited to the study of the practical aspect, but it becomes related to the concept of argumentation. For instance, human discourses, within the scope the New Rhetoric, are consideredas argumentative discourses performed during the communicative act, and aim at creating an impact on the receivers. Thus, the rhetoric of the argumentative discourse might be examined through the message delivered by the speaker to the receiver in the form of different discourses.In addition, the New Rhetoric holds that the argumentative discourse might be manifest when it expresses disagreement that entails an implicit or explicit intention, which, in turn, aims at changing the addressee's way of thinking, or exerting an impact on his positions within a non-mandatory communicative process. Therefore, whatever the nature of the discourse, whether it is about a narrative, a poetic, a religious, or a legaldiscourse, all discourses,according to the New Rhetoric,acquire in their internal linguistic structure, an argumentative dimension. Key words: Argumentative Discourse, Critics, New Rhetoric, Persuasive Discourse, Discourse Rhetoric, Thinkers.
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج04. ع.02. جامعة الوادي
Keywords: البلاغة الجديدة- بلاغة الخطاب – الخطاب الحجاجي - الخطاب ألإقناعي